Government communication and mediation strategies in environmental conflicts: Addressing church-community coalition in geothermal project - Defrida Suzana Lukuaka (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Mataloko Geothermal Power Plant in Ngada Regency, East Nusa Tenggara, exemplifies this tension, facing strong resistance from local communities and the Catholic Church despite technical potential. Since the late 1990s, the project has experienced repeated failures, causing environmental degradation, water contamination, agricultural decline, and health impacts from hydrogen sulfide exposure. Church involvement transforms this into a value-based conflict requiring ethical sensitivity. While environmental mediation is recognized as the most relevant conflict resolution mechanism in Indonesia, its effectiveness depends on government sensitivity to local social and religious contexts. Methods: This qualitative research employs systematic literature review analyzing the conflict through Johan Galtung's Conflict Theory (violence triangle), Timothy Coombs' Situational Crisis Communication Theory (crisis attribution), and Parsons' Structural-Functional Theory (AGIL paradigm). Data synthesis from academic literature, policy documents, and reports identifies conflict patterns and mediation failures. Findings: The conflict manifests fundamental contradictions between national development paradigms and local realities, including geological incompatibility, conflicts between state ownership and indigenous cosmology (mori watu mori tana), and asymmetric power relations. Government communication has been defensive rather than accommodative as required for high-responsibility crises, with transparency claims contradicted by guerrilla-style approaches and document manipulation. Mediation failed due to lack of structural independence when the provincial government formed teams involving conflicting parties. AGIL analysis reveals systemic dysfunction: adaptation failure to local conditions, contradictory goal attainment, integration breakdown, and cosmological value clashes. Conclusion: Effective environmental mediation requires transformative approaches emphasizing structural independence, forensic audits, local cosmology recognition, full accountability, and strengthened institutional capacity, demanding political will to reorient extractive paradigms toward sustainable alternatives. Novelty/Originality of this article: This research provides the first comprehensive theoretical integration specifically for geothermal conflicts involving religious institutions in Indonesia, developing a practical justice-oriented framework addressing power asymmetries, indigenous epistemologies, and prophetic witness roles in environmental governance.